1990
DOI: 10.1111/j.1471-4159.1990.tb01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peroxide, Sodium, and Calcium on Brain Mitochondrial Respiration In Vitro: Potential Role in Cerebral Ischemia and Reperfusion

Abstract: Mitochondrial pyruvate-supported respiration was studied in vitro under conditions known to exist following ischemia, i.e., elevated extramitochondrial Ca2+, Na+, and peroxide. Ca2+ alone (7-10 nmol/mg) decreased state 3 and increased state 4 respiration to 81 and 141% of control values, respectively. Sodium (15 mM) and/or tert-butyl hydroperoxide (tBOOH; up to 2,000 nmol/mg protein) alone had no effect on respiration; however, Na+ or tBOOH in combination with Ca2+ dramatically altered respiration. Respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Furthermore, sodium itself can potentiate calcium inhibition of state 3 respiration in isolated mitochondria. 30 This analysis of the free energies involved in sodium transport does not explain the apparent decrease in the sodium gradient before significant loss of ATP. Perhaps there is a large increase in inward Na + permeability preceding the full loss of ATP during ischemia.…”
mentioning
confidence: 99%
“…Furthermore, sodium itself can potentiate calcium inhibition of state 3 respiration in isolated mitochondria. 30 This analysis of the free energies involved in sodium transport does not explain the apparent decrease in the sodium gradient before significant loss of ATP. Perhaps there is a large increase in inward Na + permeability preceding the full loss of ATP during ischemia.…”
mentioning
confidence: 99%
“…It has been reported that the high metabolic rates associated with reperfusion injury can lead to excess oxygen radical production (Vlessis et al, 1990). At the onset of ischemia there is an accumulation of hypoxanthine due to breakdown of adenine nucleotides.…”
Section: Factors Associated With Excess Formation Of Cerebral Reactivmentioning
confidence: 99%
“…As described above, many studies have demonstrated that reactive oxygen species (ROS) and the resulting oxidative stress play a pivotal role in neuronal cell death (Flamm et al, 1978;Fridovich, 1979;Hall and Braughler, 1993;Kontos, 1989;Siesjo et al, 1985;Vlessis et al, 1990). There are two major regions in the electron transport chain where ROS are produced.…”
Section: Ipc and Mitochondrial Protection In The 2nd Windowmentioning
confidence: 99%
“…This hyperoxidation of electron carriers is indicative of either a response to decreased substrate availability and/or a reaction of mitochondrial complexes to reactive oxygen species (ROS) (Perez-Pinzon et al, 1997b). Postischemic mitochondrial may also be a major source of ROS, and free radical-mediated damage has been linked to reperfusion injury following brain ischemia (Flamm et al, 1978;Fridovich, 1979;Hall and Braughler, 1993;Kontos, 1989;Siesjo et al, 1985;Vlessis et al, 1990). However, recent findings suggest that this hyperoxidation may result from loss of electron carriers from mitochondria following cerebral ischemia, such as cytochrome c and NADH (Perez-Pinzon et al, 1999c).…”
Section: Neuroprotective Effects Of Ischemic Preconditioning In Brainmentioning
confidence: 99%